2016
DOI: 10.1126/science.aaf2201
|View full text |Cite
|
Sign up to set email alerts
|

Has land use pushed terrestrial biodiversity beyond the planetary boundary? A global assessment

Abstract: Copyright 2016 by the American Association for the Advancement of Science; all rights reserved.Land use and related pressures have reduced local terrestrial biodiversity, but it is unclear how the magnitude of change relates to the recently proposed planetary boundary ( safe limit ).We estimate that land use and related pressures have already reduced local biodiversity intactness-the average proportion of natural biodiversity remaining in local ecosystems-beyond its recently proposed planetary boundary across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
613
6
15

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 868 publications
(683 citation statements)
references
References 401 publications
9
613
6
15
Order By: Relevance
“…Despite growing awareness and efforts to conserve biodiversity, ecosystems worldwide are still declining (Botsford et al 1997, Vitousek et al 1997, Butchart et al 2010, Newbold et al 2016 while people still struggle to lead a life in which they themselves can decide how to improve their well-being (UNDP 2016). Policymakers and scientists too often frame the targets of diverse and productive ecosystems and healthy human societies as if they were in opposition (Raudsepp-Hearne et al 2010, McShane 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Despite growing awareness and efforts to conserve biodiversity, ecosystems worldwide are still declining (Botsford et al 1997, Vitousek et al 1997, Butchart et al 2010, Newbold et al 2016 while people still struggle to lead a life in which they themselves can decide how to improve their well-being (UNDP 2016). Policymakers and scientists too often frame the targets of diverse and productive ecosystems and healthy human societies as if they were in opposition (Raudsepp-Hearne et al 2010, McShane 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Land-use/land-cover change is among the most important factors causing biodiversity loss at the global level (e.g., Newbold et al, 2015Newbold et al, , 2016. The Mediterranean region has been affected by anthropic disturbances for thousands of years, and is, today, one of the most significantly altered hotspots in the world, with Italy following this general trend (Dalla Valle et al, 2009;Niedertscheider and Erb, 2014;Pelorosso et al, 2009;Shelef et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Species distribution models can help scientists and conservation planners estimate centres of biodiversity (Barthlott et al, 2005;Brotons et al, 2004) and identify priority areas for conservation (Elith and Leathwick, 2009) as well as patterns of major threats across the landscape, such as habitat loss, fragmentation and other anthropogenic pressures (e.g., Aben et al, 2016;Ibáñez et al, 2009;Newbold et al, 2016). In contrast, one dilemma with mapping concerns which species should be evaluated because it is impossible to map them all (Miller and Allen, 1994;Mittermeier et al, 2004;Trisurata et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Newbold et al [72] demonstrate significant advances made through the PREDICTS project (Projecting Responses of Ecological Diversity In Changing Terrestrial Systems) [73], whose researchers have compiled presence-absence and abundance data for a vast array of species in thousands of sites around the world, and concluded that the impacts on biodiversity intactness within most biomes, biodiversity hotspots and even some wilderness areas are already beyond the boundary (taking the precautionary limit of 10% reduction in BII-see Table 1). The PREDICTS database represents the most complete coverage of biodiversity response to human activity currently available, advancing beyond previous meta-analyses (e.g., GLOBIO) [74], but limitations remain, especially for facilitating future projections of biodiversity resulting from changes in land use or other changes arising from corporate decisions such as choice and sourcing of raw materials.…”
Section: Practicality Of Applying Indicators Of Biosphere Integritymentioning
confidence: 99%